LESIONES RARAS CAUSADAS PAR BRUCELLA MELITENSIS - MONCERA (Laboratorios Hormona, S A, CD MEXICO, DF, MEX, 1944)
A report on the ecological conditions of "Cueva Chica" and Cueva de los Sabinos located in the Cretaceous limestone, in the Valles region (State of San Luis Potosi, Mexico) and on the characteristics of its freshwater fauna with notes on the most importan
REV MEX MED
Keywords: LESIONES, RARAS, BRUCELLA, MELITENSIS; CIENCIAS MEDICAS; MEDICINA INTERNA; ENFERMEDADES INFECCIOSAS